Mineral Level Status of Copper, Magnesium, and Iron in Local Goat Serum Related to Keeping Pattern System - Mira Delima (Jurnal Kedokteran Hewan, 2008)
This research was conducted to find out the mineral level status of Cu, Mg, and Fe in blood serum of local goats which are reared with different methods. Blood serum was taken from 15 male and 15 female goats, 15-18 month old. The goats were divided into three groups which consist of 5 males and 5 females. Three methods of caging in which most commonly conducted by local people were selected as treatments, i.e. 1) Goats are caged only at night, while in daytime (around 10.00-12.00 WIB) they are discharged freely therefore they could foraging; 2) Goat are caged at night, while in daytime (around 10.00-18.00 WIB) they are bound with rope at which they could foraging around and, the rope would be removed several times in that particular daytime; 3) Goats are released freely all day long, but they are provided with kind of place as a cage, under the house or under the tree. Blood serum was taken from every unit sample. This research revealed that there was no significant different among methods of caging on the level rates of Cu, Mg, and Fe in local goat serum. The level rates of Cu, Mg, and Fe in goats serum that was found from the research were in normal range.